Potret Tafsir Berbasis Tarjamah: Studi Literatur Kitab Tafsir Al-Qur’an Al-Karim wa Tarjamah Mā’ānih ila Al-Lughah Al-Indunisiyah An-Nafisah - ilmiah, Dewi Bahrotul Ilmiah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This article explores a book of interpretation written by a scholar from Kediri. The interpretation presented is slightly different from the interpretations in general. Because in addition to presenting the interpretation of a verse which sometimes also presents its qawa'id al-lughoh, the interpreter of this book also contains several criticisms of several NU leaders or Islamic scholars who are considered controversial with their thoughts. This article uses descriptive analysis with library research methods and a qualitative approach. Through this approach, this article aims to deepen the understanding of the Qur'an which supports tolerance, peace, and compassion in society. This study seeks to revive the essence of the interpretation of the Qur'an in the Indonesian context as a protection against the potential for radicalization that arises due to narrow interpretation. The interpretation of the Qur'an which is unique to Indonesian culture is not only a subject of academic study, but must also be applied in real life in everyday life as a mandatory response to regional identity to existing realities.